MULTICULTURAL AND INTERCULTURAL CONCEPTS IN EDUCATION - Barbara Grabowska; Lukash Kvadrans (Borys Grinchenko Kyiv Metropolitan University, 2017)
The authors of the article make an attempt to study definitions of terms that have been around at least a few dozen years, operating in the social sciences. They suggest that multiculturalism should be treated as a form of reaction to cultural diversity. At the same time in intercultural ideas they see integration capabilities and expected form of interaction with otherness. At the end of the following article they add a short presentation of the idea of intercultural pedagogy as a scientific sub-discipline.